Bosnia and Herzegovina : Financial Sector Assessment Program-Banking Sector Stress Testing-Technical Note. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses results of Banking Sector Stress Testing for Bosnia and Herzegovina (BiH). The stress tests focused on the banking system and covered all 27 banks operating in BiH. System-wide solvency and liquidity indicators appear broadly appropriate, but significant pockets of vulnerability remain. On the basis of the supervisory data used, stress tests suggest that aggregate stress losses, mainly related to increased provisions in the loan book, although non-negligible, remain broadly manageable. Similarly, system-wide liquidity ratios appear broadly adequate. Nevertheless, there are several banks within the system-mainly small domestically owned banks-with a wide range of significant vulnerabilities. These include, low liquidity ratios, large concentration risks, and round-trip cross-border exposures.